POLA INTERAKSI EDUKATIF DALAM PENGASUHAN ANAK (STUDI KELOMPOK NELAYAN DI DESA NIBUNG KECAMATAN SELIMBAU) - Delima, Delima; Rustiyarso, Rustiyarso; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe tittle of this thesis is ?pattern of educational interaction in childcare (studies group of fishermen in village Nibung subdistrict Selimbau Kapuas Hulu)? problem in research this is how pattern of educational interactional in children. This study aims to determine shape child care for fishermen groups, within this research method used is qualitative with deskriptif. Research result 1) pattern of educational interaction within shape push and guide child, giving by motivation, coercion and persuasion. Invite their children fish, processing fish into salted fish, wey creackers and dry crackers to make money and so that children can be independent. 2) pattern of educational interaction within shape parent and child collaboration, working together to find fish, working to process fish and paerticipate the community activities. 3) pattern of educational whitin shape potential of children, develop children?s with children way make fishing gear, make wet crackers dried crackers from salted fish. 4) pattern of educational interaction within shape control children, everything a child does always control by parents, when the child is working there is good control so that no mis takes occur and if something goes wrong, it is corrected immediately.Keywords: Pattern Interaction Educative, Parenting Child, Group Fisherman.